2019
DOI: 10.1590/1678-4324-2019170518
|View full text |Cite
|
Sign up to set email alerts
|

Consortium of Microalgae for Tannery Effluent Treatment

Abstract: Wastewater generated in tanneries have essential elements for microalgae growth, but it has also some toxic compounds that may hinder or restrain the growth of microalgae in this environment. This work tested microalgae consortium growth originating from a deactivated effluent treatment decanter of a complete tannery (beamhouse to finished leather) for the treatment of wastewater of a tannery processing wet-blue leather to finished leather. It was initially evaluated the growth of the microalgae consortium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…In the authors previous study, wastewater from the finishing stage (raw wastewater, after primary and secondary treatment) was treated with a microalgae consortium. In this study it was noticed that there were removals close to P-PO 4 , NTK (Total Kjeldahl Nitrogen), NeNH 3 , and COD among the compared wastewater and a higher growth of microalgae in the raw wastewater (Pena et al, 2019). In another study from authors, Pena et al (2018) used the microalgae Tetraselmis sp.…”
Section: Introductionmentioning
confidence: 80%
“…In the authors previous study, wastewater from the finishing stage (raw wastewater, after primary and secondary treatment) was treated with a microalgae consortium. In this study it was noticed that there were removals close to P-PO 4 , NTK (Total Kjeldahl Nitrogen), NeNH 3 , and COD among the compared wastewater and a higher growth of microalgae in the raw wastewater (Pena et al, 2019). In another study from authors, Pena et al (2018) used the microalgae Tetraselmis sp.…”
Section: Introductionmentioning
confidence: 80%
“…Microalgae are autotrophic and photosynthetic aquatic microorganisms capable of synthesizing various high-value compounds, such as lipids, proteins, carbohydrates and pigments, which, together with a rapid growth rate and the ability to adapt to extreme environments, make them a viable option in the wastewater treatment [ 7 , 16 , 169 , 170 ]. This adaptive capacity allows them to grow under various conditions of acidic pH, high temperatures or excess of some compounds [ 171 ], allowing them to generate a greater amount of biomass and products of commercial interest [ 172 , 173 ].…”
Section: Technologies For the Treatment Of Tannery Wastewatermentioning
confidence: 99%
“…It has been shown that this tolerant mechanism in Chlorella and Scenedesmus strains is due to the activation of antioxidant enzymes (superoxide dismutase, catalase and ascorbate peroxidase) as a biological response to oxidative damage induced by the presence of metals [ 182 ]. However, it is not yet possible to use the crude tannery effluent as a culture medium, which can be attributed to high toxic loads and the dark color of the crude effluent, which prevents the entry of light into the medium and limits the growth of microalgae, which suggests the application of wastewater dilutions to allow better adaptation [ 16 , 183 ] and determination of the appropriate photoperiod [ 7 ].…”
Section: Technologies For the Treatment Of Tannery Wastewatermentioning
confidence: 99%
See 2 more Smart Citations